Combination of magnesium and pyridoxine: effects on hemostasis in young men with primary mitral valve prolapse - S. A. Chepurnenko (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To study the prevalence and severity of hemostasis disturbances in young men with mitral valve prolapse (MVP) and reduced compensatory and adaptive organism potential; to assess corrective therapy variants.Material and methods. In 500 young men with MVP, 16 hemostasis parameters were studied by standard methods. Among patients with reduced compensatory and adaptive potential (n=73), the combination of magnesium and pyridoxine (2 tablets 3 times per day for one month) was administered to correct functional and metabolic disturbances.Results. At baseline, platelet (PL) functional activity was 16,9 % higher than in control group. The number of spontaneous PL aggregates was 5,8 times higher, disaggregation — 47,6 % lower, and levels of paracoagulation products (fibrinogen B, fibrin-monomer complexes, soluble fibrin) — by 6,7, 4,28 and 5,3 times higher, respectively, than in controls. Reduced concentration of endogenous heparin (-94,5 %; p<0,001) and decreased antithrombin III production (-14,3 %) pointed to suppression of endogenous anticoagulant protection system. Concentrations of fibrinogen-heparin and fibrin degradation products were higher than normal levels by 2,58 and 3,38 times, respectivel. Hematocrit was 15,8 % higher, free red blood cell sedimentation — 16,4 % lower, and red blood cell aggregation — 18,64 times higher than in the control group. Therapy reduced blood coagulation potential and increased endogenous heparin activity, with parallel activation of enzyme fibrinolysis.Conclusion. Magnesium and pyridoxine therapy improved hemostasis parameters investigated. The absence of clear effect on blood rheology warrants additional administration of agents actively improving microcirculation in young men with MVP.